Pengaruh Pendapatan per Kapita dan Tingkat Suku Bunga Terhadap Jumlah Penabung di Kabupaten Kerinci - Silvia Rahayu (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
This study aims to determine the effect of per capita income and interest rates on the number of savers in Kerinci Regency. This study uses descriptive qualitative and quantitative methods including multiple linear regression and coefficient of determination. Data in this study were obtained from interviews, field observations and literature studies. From the results of the study, there was no significant effect between Per capita Income and Interest Rate on the Number of Savers in Kerinci Regency. The magnitude of the influence between Per capita Income and Interest Rate simultaneously on the Number of Savers in Kerinci Regency is 25.3%, while the remaining 74.7% is influenced by other variables not examined. Partially percapita income does not affect the number of savers in Kerinci Regency. Partially there is no significant effect between the interest rates on the number of savers in Kerinci Regency.